Pediatrics psychosocial care - Gorrie, Trula; Tirabassi, Linda; MedVid Productions (Irvine, CA : Concept Media, 1995)
(Producer) Tape 1 describes the cognitive and psychosocial development of children from birth to three years of age and uses this knowledge to develop specific interventions to decrease the negative effects of illness or injury. Tape 2 examines continued cognitive and psychosocial development and describes expected behaviors, fears, and concerns of these age groups. Illustrates methods that help prepare children for diagnostic and therapeutic procedures. Focuses on play as a means of reducing anxiety and suggests non-pharmacologic measures for alleviating pain. Tape 3 describes how a child's perception of death differs at various ages and suggests techniques the professional can use for opening a discussion about death. Addresses whether or not to tell the child when the illness is terminal and discusses the child's reaction if told. Explores hospice care as a positive option for families
1. Infants & toddlers (31 min.) -- 2. Preschool & school age children (29 min.) -- 3. The dying child (30 min.)
Some pt. titles vary on cassette labels
Writer, Trula Gorrie ; technical advisor, Linda Tirabassi
Keywords: Pediatric nursing; Child development; Child psychology; Child, Hospitalized -- psychology; Adolescent psychology; Family; Terminal Care -- infant -- Nurses' Instruction; Terminal Care -- child -- Nurses' Instruction